ANALISIS MANAJEMEN RISIKO DI UNIT SIRKULASI PERPUSTAKAAN FAKULTAS X - Surtikanti, Ratih (Jurnal Vokasi Indonesia, 2015)
The role of records management is often only realized by an organization or a person when there are problems or difficulties that can only be overcome if there is a document that contains the necessary information. analysis of effective record management so organizations can reorganize the existing record management system in accordance with the most important priority for the organization. With the improvement in the organization's records management system is expected in the foreseeable future will not encounter any problems either in the fields of law, finance, as well as the administrative history.